The Termination and Aftermath of the Lomagundi-Jatuli Carbon Isotope Excursions in the Paleoproterozoic Hutuo Group, North China - She, Z; Yang, F; Liu, W; Xie, L; Wan, Y; Li, C; Papineau, D (2015)
The Lomagundi-Jatuli Event (LJE) is one of the largest and earliest positive carbon isotope excursions preserving δ13Ccarb values between +5 and +16‰ in Paleoproterozoic carbonates worldwide. However, the duration, amplitude and patterns of these excursions remain poorly constrained. The 2.14–1.83 Ga Hutuo Group in theNorth ChinaCraton is a >10 kmthick volcano-sedimentary sequence, including >5 kmthick well-preserved carbonates that were deposited in supra-tidal to sub-tidal environments. C-O isotopic and elemental analyses of 152 least altered samples of the carbonates revealed a three-stage δ13Cevolution. It began with an exclusively positive δ13Ccarb (+1.3 to + 3.4‰) stage in the ~2.1 Ga carbonate in the Dashiling and Qingshicun Formations, followed by a transition from positive values to oscillating positive and negative values in ~3000 mthick carbonates of the Wenshan, Hebiancun, Jianancun, and Daguandong Formations, and end with exclusively negative δ13Ccarb values preserved in >500 mthick dolostones of the Huaiyincun and Beidaxing Formations. It appears that much of the LJE, particularly those extremely positive δ13Ccarb signals, was not recorded in the Hutuo carbonates. The exclusively positive δ13Ccarb values (+1.3 to + 3.4‰) preserved in the lower formations likely correspond to the end of the LJE, whereas the subsequent two stages reflect the aftermath of the LJE and the onset of Shunga-Francevillian event (SFE). The present data point to an increased influence of oxygen on the carbon cycle from the Doucun to the Dongye Subgroups and demonstrate that the termination of the LJE in the North China Craton is nearly simultaneous with those in Fennoscandia and South Africa.